AB0265 REDUCTION OF APPENDICULAR SKELETAL MASS INDEX IS A PREDICTOR OF FRACTURE IN PATIENTS WITH RHEUMATOID ARTHRITIS BASED ON THE THREE-YEAR FOLLOW-UP DATA OF THE CHIKARA STUDY. (2nd June 2020) - Tada, M.; Yamada, Y.; Mandai, K.; Hidaka, N.
Abstract : Background: Patients with rheumatoid arthritis (RA) have lower muscle mass 1 and a higher risk of fragility fracture 2 compared with healthy individuals. The predictors for fractures among baseline data and the chronological changes of disease activity, body composition, and muscle mass are unknown. Objectives: The predictors for fractures were investigated over a 3-year period in a longitudinal study. Methods: The 3-year follow-up data from a prospective observational study (CHIKARA study: Correlation researcH of sarcopenIa, sKeletal muscle and disease Activity in Rheumatoid Arthritis) were used. The patients' fractures were counted, and correlations between fractures and disease activity, body composition, and sarcopenia were investigated. Muscle mass, body fat mass, total body water, bone mass, and basal metabolic rate were measured using a body composition analyzer. The fracture-free survival rate was calculated. The relationships between fractures and each parameter at baseline and the changes over the 3-year period (Δ) were investigated by univariate and multivariate analyses. Results: A total of 100 patients (78 female, average age 68 years) were enrolled in this study; 12 patients (10 female and 2 male) had fractures during the 3-year follow-up, and the fracture-free survival rate was 86.9%. The Δmodified Health Assessment Questionnaire (mHAQ), Δweight, Δmuscle mass, Δestimated bone mass, Δbasal metabolic rate, and Δappendicular skeletal muscle index (ASMI) were predictors for fractures. On the other hand, body composition, disease activity, and sarcopenia at baseline were not correlated with fractures (Table 1 ). The ΔASMI was an independent predictor for fractures on multivariate analysis (odds ratio:0.015, P=0.026). The estimated cut-off value of the ΔASMI was 0.14 kg/m 2 on receiver operating characteristic curve analysis (Figure). When the ΔASMI decrease was greater than or equal to 0.14 kg/m 2 for three years, the odds ratio of fractures was significantly increased 9.8-fold, compared to a ΔASMI decrease less than 0.14 kg/m 2 (P=0.001). Conclusion: The fracture-free survival rate was 86.9% in this 3-year longitudinal study. It was difficult to predict future fractures from the baseline data. Reduction of the ASMI was an independent predictor for fractures. Alleviating muscle mass loss may prevent fractures. References: [1]Inui K., Koike T., Tada M., et al. Sarcopenia is apparent in patients with rheumatoid arthritis, especially those with biologics -TOMORROW study-. EULAR 2015 abstract (AB0359). [2]van Staa TP, Geusens P, Bijlsma JW, et al. Clinical assessment of the long-term risk of fracture in patients with rheumatoid arthritis. Arthritis Rheum. 2006; 54: 3104–12. Disclosure of Interests: None declared